2009
DOI: 10.2193/2008-330
|View full text |Cite
|
Sign up to set email alerts
|

Demography and Genetic Structure of a Recovering Grizzly Bear Population

Abstract: Grizzly bears (brown bears; Ursus arctos) are imperiled in the southern extent of their range worldwide. The threatened population in northwestern Montana, USA, has been managed for recovery since 1975; yet, no rigorous data were available to monitor program success. We used data from a large noninvasive genetic sampling effort conducted in 2004 and 33 years of physical captures to assess abundance, distribution, and genetic health of this population. We combined data from our 3 sampling methods (hair trap, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
359
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(377 citation statements)
references
References 48 publications
11
359
3
Order By: Relevance
“…In contrast to similar hair-snagging surveys (e.g., Kendall et al 2009), in our bear population cubs are apparently inaccessible to hair-snagging during spring and summer using traditional 50 m-high barbed wire traps (Gervasi et al 2012). Along with the overall lower capture probability of cubs (Kendall et al 2009), this is possibly due to their smaller size compared to other brown bear populations, their particularly restricted movements, and the elusive behavior of their mothers, including their lower attraction to lured traps. As a result, no cubs were detected using hair-snagging in previous surveys (Gervasi et al 2012, although cubs were indeed confirmed in the population in the same years.…”
Section: Hair-snaggingmentioning
confidence: 85%
See 3 more Smart Citations
“…In contrast to similar hair-snagging surveys (e.g., Kendall et al 2009), in our bear population cubs are apparently inaccessible to hair-snagging during spring and summer using traditional 50 m-high barbed wire traps (Gervasi et al 2012). Along with the overall lower capture probability of cubs (Kendall et al 2009), this is possibly due to their smaller size compared to other brown bear populations, their particularly restricted movements, and the elusive behavior of their mothers, including their lower attraction to lured traps. As a result, no cubs were detected using hair-snagging in previous surveys (Gervasi et al 2012, although cubs were indeed confirmed in the population in the same years.…”
Section: Hair-snaggingmentioning
confidence: 85%
“…We collected each sample possibly containing guard hairs with bulbs with sterilized surgical forceps, and placed each sample in a paper envelope labeled with a uniquely numbered barcode. We then passed a flame under the barbs to remove any trace of hair to avoid contamination between sessions (Kendall et al 2009). Paper envelopes containing samples where then stored in a dark place within a box with silica gel to avoid DNA degradation.…”
Section: Sampling Strategies and Field Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have reported using noninvasive sampling techniques to investigate population genetics and demography of wild populations 1 . This approach has proven to be especially useful when dealing with rare or elusive species 2 .…”
mentioning
confidence: 99%